Ultrasonic surgical aspiration (CUSA®) for laparoscopic excision of endometriosis: a prospective case series demonstrating safety and precision in fertility-preserving surgery - Vieira-Coimbra, Márcia; Ferreira, Hélder (Frontiers in Surgery, 2025)
IntroductionEndometriosis affects ∼10% of women of reproductive age, often causing chronic pelvic pain and infertility. Conventional energy devices risk thermal injury and bleeding, particularly in fertility-preserving surgeries. The Cavitron Ultrasonic Surgical Aspirator (CUSA®) selectively fragments tissue with minimal thermal spread. This prospective case series evaluates CUSA's safety and effectiveness in endometriosis surgery.Material and methodsFifteen women with suspected peritoneal, deep-infiltrating, or diaphragmatic endometriosis underwent laparoscopic excision exclusively using CUSA at a single center (Jan 2024–Jan 2025). Outcomes included operative time, blood loss, pain score change, recovery time, and complications.ResultsMean CUSA time was 8.5 ± 3.0 min with a median blood loss was less than10 mL. No intraoperative complications or conversions occurred. Surgeon-reported performance scores demonstrated high procedural efficiency and manageable technical challenges. At the first follow-up visit (6–8 weeks postoperatively), Numeric Pain Rating Score decreased by 3.2 points from 6.9 ± 1.4 to 3.7 ± 1.0, indicating marked symptom relief. All patients resumed daily activities within 3 days. In all patients, all visible lesions suggestive of endometriosis were excised intraoperatively, and histology confirmed endometriosis in all cases. Discussion: CUSA allows precise and safe laparoscopic excision of endometriosis with minimal bleeding, absence of perioperative complications, and significant short-term pain reduction. These findings demonstrate the feasibility and short-term safety of the technique and support its potential value in fertility-preserving surgery. However, given the small sample size, single-center design, and limited follow-up, the results should be interpreted with caution. Future multicenter studies with larger cohorts and reproductive outcome assessment are needed to confirm these preliminary findings.